Benefits and risks of manual hyperinflation in intubated and mechanically ventilated intensive care unit patients: a systematic review - Paulus, Frederique (BioMed Central, 2012)
INTRODUCTION: Manual hyperinflation (MH), a frequently applied maneuver in critically ill intubated and mechanically ventilated patients, is suggested to mimic a cough so that airway secretions are mobilized toward the larger airways, where they can easily be removed. As such, MH could prevent plugging of the airways. METHODS: We performed a search in the databases of Medline, Embase, and the Cochrane Library from January 1990 to April 2012. We systematically reviewed the literature on evidence for postulated benefits and risks of MH in critically ill intubated and mechanically ventilated patients. RESULTS: The search identified 50 articles, of which 19 were considered relevant. We included 13 interventional studies and six observational studies. The number of studies evaluating physiological effects of MH is limited. Trials differed too much to permit meta-analysis. It is uncertain whether MH was applied similarly in the retrieved studies. Finally, most studies are underpowered to show clinical benefit of MH. Use of MH is associated with short-term improvements in lung compliance, oxygenation, and secretion clearance, without changes in outcomes. MH has been reported to be associated with short-term and probably clinically insignificant side effects, including decreases in cardiac output, alterations of heart rates, and increased central venous pressures. CONCLUSIONS: Studies have failed to show that MH benefits critically ill intubated and mechanically ventilated patients. MH is infrequently associated with short-term side effects.